Faktor-faktor yang mempengaruhi tunggakan pajak kendaraan bermotor Kabupaten Tanjung Jabung Barat (studi kasus: Kecamatan Tungkal Ilir) - Oktavia, Eymilia; Safri, Muhammad; Vyn Amzar, Yohanes (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2019)
This study aims to identify and analyze: 1) the characteristics of PKB arrears in terms of age, education level, income, and the motor vehicle tax service system (PKB) in Tungkal Ilir District and 2). The influence of age, education level, income, and the motor vehicle tax service system (PKB) on motor vehicle tax arrears in Tungkal Ilir District. The data analysis method used in this study used a descriptive and regression analysis model. Based on the results of the study, it was obtained: The characteristics of the respondents in this case the individual motorized vehicle taxpayers (PKB) in Tungkal Ilir District were: the average age of the respondents in this study was 33 years, the average education level of the respondents is high school/equivalent and the average monthly income/income is Rp. 2,486,000. Age (U) has a positive and significant effect on arrears of Motor Vehicle Taxes, while the level of education (TP), income (P), and the tax service system (SP) has a negative and significant effect on arrears of Motor Vehicle Taxes in Tungkal Ilir District, both together -equally or partially. Keywords: Tax arrears, Motor vehicles, Multiple regression analysis